Pharmacogenomics of episodic migraine: time has come for a step forward. (March 2014) - Viana, Michele; Terrazzino, Salvatore; Genazzani, Armando A; Grieco, Gaetano S; Cargnin, Sarah; Santorelli, Filippo M; Pierelli, Francesco; Tassorelli, Cristina; Nappi, Giuseppe; Di Lorenzo, Cherubino
Migraine is characterized by heterogeneous behavior in response to drugs. Many resources have been invested in attempting to unravel the genetic basis of migraine, while the role of genetics in responses to currently available drugs has received less attention. We performed a systematic literature search identifying original articles pertaining to pharmacogenomics of episodic migraine. Few primary studies on the pharmacogenomics of symptomatic and preventive medication in episodic migraine were found. The number of patients studied in the individual articles ranged from 40 up to 130. There was a strong heterogeneity among these studies. We believe that pharmacogenomics studies, if properly designed, could contribute towards optimizing the treatment and reducing the burden of migraine, in turn helping patients and optimizing resources. Our knowledge on the pharmacogenomics of migraine is growing too slowly, and concerted measures should be undertaken to speed up the process.